2014
DOI: 10.1002/2012tc003224
|View full text |Cite
|
Sign up to set email alerts
|

Active tectonics in Quito, Ecuador, assessed by geomorphological studies, GPS data, and crustal seismicity

Abstract: The Quito Fault System (QFS) extends over 60 km along the Interandean Depression in northern Ecuador. Multidisciplinary studies support an interpretation in which two major contemporaneous fault systems affect Quaternary volcanoclastic deposits. Hanging paleovalleys and disruption of drainage networks attest to ongoing crustal deformation and uplift in this region, further confirmed by 15 years of GPS measurements and seismicity. The resulting new kinematic model emphasizes the role of the N-S segmented, en ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 40 publications
3
89
0
6
Order By: Relevance
“…The east is limited by several hills which are Puengasí (P), Ilumbisí-La Bota (ILB), towards north the Inca Calderon hill (CEI), and at the north the BellavistaCatequilla (BC), where the last moderately strong earthquake of 12 August 2014 originated, which had a magnitude of 5.1 and focal depth of 5 km (Aguiar et al, 2014). The Guayl- (Alvarado et al, 2014). labamba basin, GB, can also be observed.…”
Section: Blind Faults In Quitomentioning
confidence: 93%
See 3 more Smart Citations
“…The east is limited by several hills which are Puengasí (P), Ilumbisí-La Bota (ILB), towards north the Inca Calderon hill (CEI), and at the north the BellavistaCatequilla (BC), where the last moderately strong earthquake of 12 August 2014 originated, which had a magnitude of 5.1 and focal depth of 5 km (Aguiar et al, 2014). The Guayl- (Alvarado et al, 2014). labamba basin, GB, can also be observed.…”
Section: Blind Faults In Quitomentioning
confidence: 93%
“…(meters above sea level) and the valleys are 2400 m. The hills P, ILB, CEI, and BC have heights that vary between 100 and 300 m. They are the external signs of the existence of blind reverse faults that raise from 2 to 4 mm yr −1 (Alvarado et al, 2014) and are shown in Fig. 3.…”
Section: Blind Faults In Quitomentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 2 shows a numerical calculation model of possible fault planes that could be generated in the case of earthquakes occuring with a burst length equal to the maximum distance of each of the fault segments. The model assumes that these events are not produced simultaneously (Alvarado et al 2014;Rivas et al 2014). The fault planes are shown projected in a horizontal plane.…”
Section: Introductionmentioning
confidence: 99%